Heterozygous IGFALS Gene Variants in Idiopathic Short Stature and Normal Children: Impact on Height and the IGF System - Domene, Horacio Mario (2013)
Background: In acid-labile subunit (ALS)-deficient families, heterozygous carriers of IGFALS gene mutations are frequently shorter than their wild-type relatives, suggesting that IGFALS haploinsufficiency could result in short stature. We have characterized IGFALS gene variants in idiopathic short stature (ISS) and in normal children, determining their impact on height and the IGF system. Patients and Methods: In 188 normal and 79 ISS children levels of IGF-1, IGFBP-3, ALS, ternary complex formation (TCF) and IGFALS gene sequence were determined. Results: In sum, 9 nonsynonymous or frameshift IGFALS variants (E35Gfs*17, G83S, L97F, R277H, P287L, A330D, R493H, A546V and R548W) were found in 10 ISS children and 6 variants (G170S, V239M, N276S, R277H, G506R and R548W) were found in 7 normal children. If ISS children were classified according to the ability for TCF enhanced by the addition of rhIGFBP-3 (TCF+), carriers of pathogenic IGFALS gene variants were shorter and presented lower levels of IGF-1, IGFBP-3 and ALS in comparison to carriers of benign variants. In ISS families, subjects carrying pathogenic variants were shorter and presented lower IGF-1, IGFBP-3 and ALS levels than noncarriers. Conclusions: These findings suggest that heterozygous IGFALS gene variants could be responsible for short stature in a subset of ISS children with diminished levels of IGF-1, IGFBP-3 and ALS.